Soccer coaches understanding of talent in soccer - Sæther, S.A. (ISHPES & ISSA, 2007)
Introduction: According to Russell (1989) talent identification refers to the process of recognizing current participants by their potential to become elite players. Some researchers have argued that the concept of talent is a myth (Howe et al.1998). The aim of this study was to investigate how soccer coaches understand the concept of talent. Methods: Participants (N=14) in this study where all elite coaches at the premier level in Norwegian soccer. All of the interviews were conducted by telephone and within a two-week period at the start of the year in February 2004. The coaches was asked to rank five skills from most to least important. They were also asked which types of skills they were looking for when they were identifying talents and players to their own squad. Results: The results showed that coaches valued the technical and tactical skills as most important when they identify talent. On the other end of the scale the coaches regarded the physical and the social skills as least important. Some coaches answered in a conflicting manner when comparing criteria`s for identifying talent and the criteria`s emphasized when selecting their own squad. Discussion/Conclusions: This study concludes that soccer coaches at the premier level have different and partially conflicting understandings of talent. Criteria`s used by coaches to identify talent seem random according to the findings of this study